Improving EFL Students’ Performance in Reading Comprehension Through Explicit Instruction in Strategies - Uribe Enciso, Olga (Rastros Rostros, 2015)
Introduction: Explicit instruction in reading strategies has been recommended to improve reading comprehension in both L1 and L2 formal educational settings for over 20 years. The purpose of this study was to determine the effectiveness of a proposal for teaching reading strategies explicitly to efl students, in terms of strategy recognition and performance in reading comprehension tasks. Methodology: The research is conducted to solve language learning problems and follows a mixed-method approach since both qualitative and quantitative data was collected and analyzed through questionnaires, reading tests and tasks. Besides, purposive sampling was used to select participants, and both qualitative and quantitative data was collected through questionnaires, reading tests and tasks. Results: After the sixteen-week training, the participants reported wider reading strategy repertoires and higher scores in the reading comprehension Exit Test. Conclusions: Explicit instruction in reading strategies is effective to improve reading comprehension. Further research is suggested to test the effectivity of the model with other students and to find out if learners in this study continue using the reported strategies consistently and autonomously.
Keywords: reading comprehension; reading strategies; explicit instruction; l2 reading, pip (pre-, in/while, post-)